Snare-Assisted Retrieval of an Embolized Broken Double Lumen from the Heart of a Female Patient Diagnosed with End Stage Kidney Disease: A Case Report - Yaseen , Manaf Jarallah (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Foreign body embolization is a rare but serious iatrogenic complication that might necessitate transcatheter or even surgical retrieval. A broken double-lumen catheter was snared using a goose neck snare kit. The procedure was successful, and the patient experienced no further complications.